O uso da cannabis sativa (maconha) pelo filho e suas repercussões nas relações familiares - Mangueira, Renata Torres da Costa (2005)
The fact of having a drug user in the family compromises its organization, interfering in the quality of its relations. The drug use revelation is a crucial moment in the relationships between the user and his relatives; all the further conduct will depend on how this moment has been. Not until recently have there been in Brazil studies of the relation between the Cannabis sativa users and their families. The increase of researches and the practice in this area may be another alternative to treating dependency, which confirms the relevance of our research. This paper aims generally at performing a study case of a familiy whose son is a user of Cannabis sativa (marijuana). More specifically it aims at: 1. analyzing how relatives deal with the use of Cannabis sativa by the son; 2. investigating how the user accepts the requests of his family about drug use; 3. studying what happens in this family, when the use of Cannabis sativa is revealed by the son. In the research, we had contact with one user at Eulâmpio Cordeiro Human Rehabilitation Center (CECRH) one institution for users and / or people dependent on psychoactive substances in the public health care system of the state of Pernambuco as well as with his relatives. The work was developed based on the General Systems Theory and used the semidirect interview aproach. The conclusions of our paper have shown that since the moment in which the revelation of drug use is understood by the family, the son starts to have a central role in the family relations. Matters of significant importance to this family and that had not been discussed so far, such as the falt that the user was born to substitute a sister who passed away precociously; the parents absence of care for the life of the son; the abundant use of alcoholic drinks by the family; the father s and granfather s alcohol dependency; as well as the use of Cannabis sativa by the cousin, led to the search for a healthier life among the members of this family, which is intensily disfuncional in its systemic properties. We have concluded that family therapy is essential for the user s family, so that this system can work properly again, thus, solving the differences and restoring the harmony among its members